The The Role of Pancasila as a Political Ethical System: Understanding Indonesia's Ideological Foundation and Moral Guidance - Azkiyah S, Hilda; Nurnisaa AS (Communication in Research and Publications (CRP), 2024)
This research discusses the role of Pancasila as a political ethical system in Indonesia. Political ethics is a branch of philosophy that discusses human behavior in a political context, which cannot be separated from aspects of morality and basic human values ​​as its subject. Pancasila, as the basis of the state and ideology in Indonesia, is also a source of values ​​and principles in political implementation. The basic values ​​of Pancasila such as Belief in One Almighty God, Just and Civilized Humanity, Indonesian Unity, Democracy Led by Wisdom in Deliberation/Representation, and Social Justice for All Indonesian People are the moral foundation in political ethics. With the principles of legality, democracy and morality, Pancasila demands that state power be exercised in accordance with moral principles and justice for all Indonesian people.